The quality of financial information in light of the Financial Accounting System and International Accounting Standards - a case study of listed Algerian companies - beghriche, mohamed; beladjouz, hocine (Journal of Research in Finance and Accounting, 2026)
This study aimed to know the impact of the adoption of the Financial Accounting System (SCF) and International Accounting Standards (IAS) on the quality of financial information. By studying the quality of financial information in some countries which have adopted these standards; using a documentary survey approach. And studying the quality of financial information in light of the SCF; by analysing the financial statements and reports of Algerian listed companies for the period 2015-2018; using the dummy variables method. The study found that the adoption of the SCF and IAS had a positive impact on the quality of financial information; but this impact is linked to the accounting environment; as well as how the SCF and IAS should be understood and adhered to.